Influence of smoking on disease severity and antimalarial therapy in cutaneous lupus erythematosus: analysis of 1002 patients from the EUSCLE database. (25th August 2014) - Kuhn, A.; Sigges, J.; Biazar, C.; Ruland, V.; Patsinakidis, N.; Landmann, A.; Amler, S.; Bonsmann, G.; ,
Summary: Background: In recent years it has been controversially discussed in the literature if smoking is associated with the activity of cutaneous lupus erythematosus (CLE) and the efficacy of antimalarial agents. Objectives: To investigate the influence of smoking on disease severity and antimalarial treatment in patients with CLE using the Core Set Questionnaire of the European Society of Cutaneous Lupus Erythematosus (EUSCLE). Methods: A total of 1002 patients (768 female, 234 male) with different CLE subtypes were included in this cross‐sectional study, which was performed in 14 different countries. Smoking behaviour was assessed by the EUSCLE Core Set Questionnaire in 838 patients and statistically analysed using an SPSS database. The results were correlated with the Cutaneous Lupus Erythematosus Disease Area and Severity Index (CLASI) and the efficacy of antimalarial treatment. Results: A high percentage (87·2%) of the 499 patients with CLE, who have ever smoked, had already smoked at the date of their first diagnosis. Patients with intermittent CLE have ever smoked significantly more often than patients with subacute CLE ( P < 0·05) and chronic CLE ( P < 0·05). The total CLASI activity and damage score of patients with CLE was 6·6 ± 7·1 and 2·6 ± 4·3, respectively, and was higher in patients who have ever smoked than in nonsmokers. Antimalarial treatment was successful in 84·3% of cases, with a significantly higher efficacy in nonsmokers than in patients with CLE who have ever smoked ( P < 0·05). Conclusions: This analysis of a multicentre study population of 838 patients with CLE assessed by the EUSCLE Core Set Questionnaire confirms that smoking negatively influences CLE disease severity and the efficacy of antimalarial treatment. Abstract : What's already known about this topic? The influence of smoking on disease severity in patients with cutaneous lupus erythematosus (CLE) and the efficacy of antimalarial treatment is still being controversially discussed in literature. What does this study add? The present analysis of a study population of 838 patients with CLE suggests that smoking is a risk factor for the disease, in particular for intermittent CLE. The results confirm that there is a negative influence of smoking on disease severity and that the efficacy of the antimalarials hydroxychloroquine and chloroquine is affected by smoking.